STRESS AMONG FIRST MBBS STUDENTS OF SHRI BHAUSAHEB HIRE GOVERNMENT MEDICAL COLLEGE, DHULE. - DR.A.R.RANADE,; DR.S.R.DHANUMALI, (International Journal of Pharma and Bio Sciences, 2015)
Stress in medical students is not uncommon. The present study had the aim to find out different stress factors among the first M. B. B. S. Students. A cross sectional study using pre designed questionnaire was done in Department of physiology, Sri Bhausaheb Hire Govt. medical college, Dhule. Total 70 students were asked to complete the questionnaire that included a list of sources of stress. Questionnaire was analysed by CHI square test. The most stressful factors reported by participants were conflict of not getting enough leisure time, academic performance, financial Pressure and school attendance. There is no single causative factor responsible for specific grades of stress. All stressful factors contribute to stress in same proportion. Most common symptoms of stress were Poor concentration, Headache, restlessness, sudden change in mood, lack of sleep, low energy & fatigue. This study demonstrated first year medical students were at various levels (grades) of stress.